Impact of Sand on Hydraulic Turbine Material: A Case Study of Roshi Khola, Nepal - Poudel, Laxman Prasad; Thapa, Bhola; Shrestha, Bim Prasad; Shrestha, Nabin Kumar (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
Nepal is endowed by enormous water resources andpower potential, but not enough energy has been exploited from it. One reason is the deterioration of hydraulic turbines. Research on turbine erosion has shown that sand erodes the turbine material. Only a few researches however, have provided details of the many parameters of sand on the degradation of hydraulic turbines. This paper describes the different parameters of sand and the direct impact of sand on turbine material. The study of sand of the Roshi Khola (river) in Nepal shows that mineral content, size, shape and texture are the most important parameters of sand, with different characteristics and their impact on hydraulic turbines. Different methods like using a sieve analyzer to characterize size, microscopic observation after acid wash technique to characterize mineral content, and image processing to characterize and count particle shape are utilized to characterize sand. Sand samples from 20 stations on the Roshi Khola are used in this study. Most of the sampling locations are proposed hydropower project sites and confluences of tributaries. The erosion tests were carried out on turbine material in a High Velocity Erosion Test Rig at Kathmandu University. It was found that hardness, size, and shape are important parameters concerning their effects on erosion of hydraulic turbines. Even a short river like the Roshi Khola shows different sand characteristics at different locations and that they have different erosion rates. DOI: http://dx.doi.org/10.3126/hn.v10i0.7116 Hydro Nepal Vol.10 January 2012 60-65